Characterizing a pH‐switch anti‐C5 antibody as a tool for human and mouse complement C5 purification and cross‐species inhibition of classical and reactive lysis. Issue 3 (30th July 2018) - Zelek, Wioleta M.; Stott, Matthew; Walters, David; Harris, Claire L.; Morgan, B. Paul
Summary: C5 plays a major role in complement activation; C5 convertase cleaves C5 into the pro‐inflammatory C5a, and C5b, the nidus for the formation of the lytic membrane attack complex. C5 is a major target for anti‐complement drugs, necessitating better methods for the study of C5 function. Purification of C5 is complicated; classical methods involve precipitation or pH shifts that result in functional loss and low yield. We here present a method for C5 purification using a novel anti‐C5 monoclonal antibody (mAb); RO7112689 (C5i mAb, SKY59), pH‐switch engineered to induce antibody–antigen dissociation in the acidic endosome ( pH 5·5). RO7112689 was bound on an affinity column; applied serum was completely depleted of C5. Elution at pH 5 produced fully active C5 at 98% yield. The mAb also bound C5b in the C5b6 complex, preventing C5b6 binding to target membranes and enabling purification of C5b6 from activated serum. RO7112689 inhibited C5 in mouse serum and efficiently purified mouse C5. Used as capture, RO7112689 produced sensitive and specific assays for human and mouse C5. This novel antibody enables efficient production of intact, fully active, pure human and mouse C5, and quantification of C5 in these species. The demonstration that RO7112689 binds C5b6 adds an additional mechanism of membrane attack complex inhibition by this mAb. Abstract : 'RO7112689 (anti‐C5 antibody) enables rapid production of intact and fully active human and mouse C5 at high purity. The antibody specifically bound and inhibited both C5 and C5b6, suggesting an additional activity for this antibody beyond inhibition of C5 cleavage that may enhance its therapeutic effect'.